ANALISIS IMPLIKASI KERJASAMA SISTER CITY YOGYAKARTA DAN GYEONGSANGBUK-DO DALAM PEMBENTUKAN KOTA TANGGUH MELALUI PROGRAM SAEMAUL UNDONG - Aditya Maulana Hasymi; Gardyas Bidari Adninda; Megan Alvira Putri; Diva Suci Ariani (Jurnal Dinamika Global, 2024)
One strategic approach to address the issue of changing global political configurations is foreign collaboration by cities through local governments. Through a cooperation with the South Korean city of Gyeongsangbuk-do, Yogyakarta was able to implement the sister city foreign relations, which has the ability to address regional issues. Literature reviews and in-depth interviews were used in this study to determine the effects on the community of the Saemaul Undong program's creation of resilient cities. This research aims to determine the implications of sister city between Gyeongsangbuk-do and Yogyakarta on the development of resilient cities under the Saemaul Undong program. According to the perspective of resilient cities, the implications of sister city cooperation on resilient cities is reflected in the synergy of participatory roles between the elements involved based on the institutional liberalism approach, as well as the increase in community resilience through community economic growth.